A micro-method for the detection of butyrylcholinesterase secreted by hepatocytes in vitro. Issue 2 (February 1984) - Schuman, Richard F.; Brimfield, A. A.; Hunter, Kenneth W.
Abstract : A new assay has been developed for detection of butyrylcholinesterase (EC 3.1.1.8) activity based upon the change in absorbance of phenol red, caused by the release of butyric acid from the substrate. Using commercially available enzyme prepared from horse serum, linear, dose-related decreases in absorbance were obtained, generally with correlation values of 0.965 or greater. The assay was modified and used to detect enzyme activity in the supernatants from primary cultures of mouse hepatocytes. The enzyme-mediated response was inhibited by NN′-diisopropylphosphorodiamidic anhydride, a specific inhibitor of butyrylcholinesterase.